Nonstandard Maternal Work Schedules: Implications for African American Children’s Early Language Outcomes - Odom, Erika C. (2013)
In this study, observed maternal positive engagement and perception of work-family spillover were examined as mediators of the association between maternal nonstandard work schedules and children’s expressive language outcomes in 231 African American families living in rural households. Mothers reported their work schedules when their child was 24 months of age and children’s expressive language development was assessed during a picture book task at 24 months and with a standardized assessment at 36 months. After controlling for family demographics, child, and maternal characteristics, maternal employment in nonstandard schedules at the 24 month timepoint was associated with lower expressive language ability among African American children concurrently and at 36 months of age. Importantly, the negative association between nonstandard schedules and children’s expressive language ability at 24 months of age was mediated by maternal positive engagement and negative work-family spillover, while at 36 months of age, the association was mediated only by negative work-family spillover. These findings suggest complex links between mothers’ work environments and African American children’s developmental outcomes.